Leading with Cultural Intelligence - Moua, Mai (Open textbook library., 2012)
Organizations in the 21st century are in need of culturally intelligent managers and leaders. The pressure to build authentic global networks and to cultivate an appreciation and respect for cultural differences and similarities has driven cultural intelligence to the forefront of diversity and inclusion work. Preparing today's students to be effective leaders in their professional lives requires that they hone their cultural intelligence as it is vital to working inter- and intra-culturally in today's global economy. This unique ability to identify, recognize, and acknowledge the differences and similarities that exist between and among cultural groups and systems will set their leadership skills apart from the masses. And when applied, cultural intelligence can bridge the gap in cultural misunderstanding by creating awareness, knowledge, and patience of cultural norms and behaviors. The purpose of Leading With Cultural Intelligence by Mia Moua is to outline the important ideas of cultural intelligence and the steps that must be considered and then practiced to become a culturally intelligent leader. The most important aspect covered within this book is that cultural intelligence is both a strategy and a tool towards cultural competency and proficiency. This book outlines the importance of understanding culture and its impact on organizations, the strategic value of cultural intelligence, and the significance of integrating and practicing cultural intelligence in everyday business life. When all these aspects are properly integrated and applied in the leadership and management process, organizations are more innovative and adaptable to respond to cultural changes.